2021
DOI: 10.21037/atm-20-5472
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of hepatectomy-related complications and prediction model for postoperative liver failure after major liver resection in 1,441 patients without obstructive jaundice

Abstract: Background: This cohort study, based on a large sample of extensive hepatectomy cases, aimed to analyze the distribution of hepatectomy-related complications and to develop a predictive model of posthepatectomy liver failure (PHLF).Methods: Data of patients who underwent hepatectomy of ≥3 liver segments at the Eastern Hepatobiliary Surgery Hospital from 2000 to 2016 were collected and analyzed. Information on hepatectomy-related complications was collected and risk factors were analyzed. A total of 1,441 eligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…As no tool exists to predict PHLF after major hepatectomy for HCC, this predictive model might serve as a quantitative scoring system to individually estimate the risk of PHLF and to select HCC patients for major hepatectomy. PHLF was one of the most common complications and the leading cause of mortality after PH, particularly in patients who underwent major hepatectomy (3)(4)(5)(6)(7)24). In the present study, 155 (22.5%) and 37 (19.3%) patients in the training and validation cohorts met the ISGLS criteria for PHLF, respectively.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…As no tool exists to predict PHLF after major hepatectomy for HCC, this predictive model might serve as a quantitative scoring system to individually estimate the risk of PHLF and to select HCC patients for major hepatectomy. PHLF was one of the most common complications and the leading cause of mortality after PH, particularly in patients who underwent major hepatectomy (3)(4)(5)(6)(7)24). In the present study, 155 (22.5%) and 37 (19.3%) patients in the training and validation cohorts met the ISGLS criteria for PHLF, respectively.…”
Section: Discussionmentioning
confidence: 52%
“…Although postoperative morbidity and mortality have decreased over the past decades with advances in surgical techniques and perioperative management (1,2), they remain high in HCC patients who underwent major hepatectomy. Previous studies have revealed that post-hepatectomy liver failure (PHLF) is one of the most seriously complications and the main cause of mortality particularly in patients undergoing major hepatectomy (3)(4)(5)(6)(7). Therefore, accurate preoperative prediction of the risk of PHLF is essentially important for patient selection and perioperative management.…”
Section: Introductionmentioning
confidence: 99%
“…A multicentric retrospective analysis of patients with hepatocellular carcinoma who underwent major hepatectomy (≥ 3 segments) from the Eastern Hepatobiliary Surgery Hospital in Shanghai, Zhongda Hospital, Southeast university in Nanjing, Qin Huai Medical District of Eastern Theater General Hospital in Nanjing and The First Affiliated Hospital of Xi'an Jiao Tong University in Xi'an between January 01, 2008 and December 31, 2019 were recorded. Inclusion criteria are obeyed strictly as follows: (1) pathologically confirmed as hepatocellular carcinoma; (2) underwent major hepatectomy, major hepatectomy is defined as resection of Couinaud's segmentation 3 and above 4 ; (3) no anti-tumor treatment before surgery, such as ablation, TACE; (4) no major blood vessel invasion, bile duct cancer thrombus and distant metastasis; (5) age ≥18. Exclusion criteria: (1) intraoperative radiofrequency ablation, particle placement and other treatments; (2) data were missing on the fifth day after surgery, and PHLF could not be defined.…”
Section: Methodsmentioning
confidence: 99%
“…(2) underwent major hepatectomy, major hepatectomy is defined as resection of Couinaud's segmentation 3 and above [4]; (3) no anti-tumor treatment before surgery, such as ablation, TACE; (4) no major blood vessel invasion, bile duct cancer thrombus and distant metastasis; (5) age ≥18. Exclusion criteria: (1) intraoperative radiofrequency ablation, particle placement and other treatments; (2) data were missing on the fifth day after surgery, and PHLF could not be defined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation